Between family conflict and school violence. A vision in the students of high school education of popular sectors in Lima. - Jacinto Pazos, Pedro (2019)
The manifest forms of verbal or psychological aggression are analyzed, in direct conjunctionwith physical aggression, which are observed constantly, in the familiar areas of the popularsectors and, which are reproduced in school. In fact, the students admit physical aggressionin the home, with figures close to fifty percent in the districts investigated, including withit, the verbal aggression from a majority percentage sense. Of course, what schoolchildrenobserve is a very violent and aggressive home in its different forms, which a large part of thestudents find it impossible to deny. It is manifested, the violence from the parents, but alsowith more rawness the confrontation between the brothers. Not far from all this, communityor neighborhood violence, which also projects alarming figures and that students perceivedaily. It is not a linearity, thinking about explaining the family conflict and its effects on schoolviolence, but warning, the high figures that involve physical aggression in school spaces.